2005
DOI: 10.1038/sj.cr.7290269
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pancreatitis, pancreatic adenocarcinoma and the black box in-between

Abstract: Pancreatic cancer is a challenging disease for patients, doctors and researchers who for decades have searched for a cure for this deadly malignancy. Although existing mouse models of pancreatic cancer have shed light on the mechanistic basis of the neoplastic conversion of the pancreas, their impact in terms of offering new diagnostics and therapeutic modalities remains limited. Chronic pancreatitis is an inflammatory disease of the pancreas that is associated with a gradual damage of the organ and an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
58
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 35 publications
0
58
0
1
Order By: Relevance
“…However, it has been estimated that only approximately 25-30% of pancreatic cancer cases in the United States are related to cigarette smoking (6,9). Other factors such as diabetes mellitus, alcohol consumption, and chronic pancreatitis have also been examined for a relationship to pancreatic cancer (5,9,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). However, to our knowledge, no research has been done to determine whether the associated risk of each factor varied by sex.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been estimated that only approximately 25-30% of pancreatic cancer cases in the United States are related to cigarette smoking (6,9). Other factors such as diabetes mellitus, alcohol consumption, and chronic pancreatitis have also been examined for a relationship to pancreatic cancer (5,9,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). However, to our knowledge, no research has been done to determine whether the associated risk of each factor varied by sex.…”
Section: Introductionmentioning
confidence: 99%
“…Association between chronic inflammation and the development of cancer has been recognized for several years (14)(15)(16)(17)(18). Various cytokines, such as tumor necrosis factor-a (TNF-a) and interleukin-1 (IL-1), which seem to play roles in inflammatory responses and the fibrotic reaction, are overexpressed in pancreatic cancer (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Although these studies concern the usage of both GLP-1 mimetics and the orally administered gliptins, and our study exclusively focusses on gliptins, and is not concerned with the GLP-1 mimetics data. The close relationship between chronic pancreatitis and pancreatic cancer is also a subject of intense research 45 . Another administrative database study of US adults with type 2 diabetes reported increased odds of hospitalization for acute pancreatitis for patients undergoing GLP-1 based therapies sitagliptin 13 .…”
Section: Discussionmentioning
confidence: 99%